The role of the circadian clock in rheumatoid arthritis - Gibbs, Julie E (BioMed Central, 2013)
Rheumatoid arthritis exhibits diurnal variation in symptoms, with patients suffering with increased painful joint stiffness in the early morning. This correlates with an early morning rise in circulating levels of pro-inflammatory cytokines, such as interleukin-6. This temporal variation in disease pathology is directed by the circadian clock, both at a systemic level, through signalling pathways derived in the central clock, and at a local level by autonomous clocks found within inflammatory organs and cells. Indeed, many cellular components of the immune system, which are involved in the pathogenesis of rheumatoid arthritis, possess independent clocks that facilitate temporal gating of their functions. Furthermore, the circadian clock regulates the expression and activity of several genes and proteins that have demonstrated roles in progression of this autoimmune disease. These include a number of nuclear receptors and also fat-derived adipokines. Employing the knowledge we have about how the inflammatory response is regulated by the clock will facilitate the development of chronotherapy regimens to improve the efficacy of current treatment strategies. Furthermore, a full understanding of the mechanisms by which the clock couples to the immune system may provide novel therapeutic targets for the treatment of this debilitating disease.